Protection from misleading advertisement under the Jordan Civil Law 1976 and the draft Law of Consumer Protection 2013 - Mohammad Alsharu, Ahmad Ibrahim; Mohd Noor, Fauziah; Abdul Rahman, Rohana (Asian Business Consortium, 2019)
Commercial advertisements play a crucial role in identifying features and specifications of goods and products. However, misleading advertising has become one of main forms unfair practise customers/ consumers. Jordan considered as one of the countries that does not have rules and provisions that regulate the consumer protection specifically misleading advertisements. This paper discussed about the Jordanian laws in protecting the consumer from misleading advertisements. The objective of the article to examine how the Jordanian provisions by the Civil law 1976 and the Jordanian Draft law of Consumer Protection 2013 protect consumers from misleading advertisements in Jordan. This paper has examined the subject of consumer protection in misleading advertisement and the provisions available in Jordan as protection to consumers from misleading advertisements. In order to achieve this purpose, the existing rules and laws, facts, principles, concepts and the law provisions has been examined and analyzed